Investigation and risk assessment of fluoride concentration in drinking water, soil and food products in Hamedan rural areas - Ghorban Asgari; Mehdi salari; Abdolmotaleb Seidmohammadi; Behroz Akbari-adergani; Amir Hossein Mahvi; Naser Kamari; Khadije Ezzati Rastegar; Hossein Faraji (Scientific Reports)
Abstract The high concentration of fluoride in the soil can serve as a pathway for this element to enter the body through food products. The purpose of this research was to investigate the fluoride concentrations in drinking water sources, regional soil, and cultivated vegetables (tomatoes, cucumbers, onions, and potatoes), as well as to assess the relationship between fluoride concentration in drinking water and fluoride content in food products. Additionally, the study aimed to evaluate the risk of exposure using a Monte Carlo simulation in Hamadan. This cross-sectional analytical study was conducted in 2021 in Hamadan. To assess water fluoride levels in different villages, 26 wells were selected. After evaluating the fluoride concentrations, two areas with water fluoride levels above the standard were identified, along with two areas with fluoride levels below the standard. From these four agricultural sites, three soil samples were collected from each location, resulting in a total of 24 soil samples. For each site, three samples of cultivated vegetables (tomatoes, cucumbers, onions, and potatoes) were also collected, yielding a total of 92 samples from areas with both high and low water fluoride concentrations. Fluoride analysis in drinking water was performed using the SPADNS method, while the fluoride content in vegetables was measured with a standard ion-selective electrode method. The results indicated that the average fluoride concentrations in the high-fluoride area for drinking water, tomatoes, onions, cucumbers, and soil were as follows: 3.5 ± 0.5 mg/L, 2.38 ± 0.15 mg/kg, 1.89 mg/kg, 0.39 ± 0.05 mg/kg, and 110.5 ± 0.03 mg/kg, respectively. In contrast, the average concentrations in the low-fluoride area were 0.3 ± 0.1 mg/L for drinking water, 11.0 ± 0.009 mg/kg for tomatoes, 1.29 ± 0.5 mg/kg for onions, 98.05 ± 0.02 mg/kg for cucumbers, and 1.6 ± 0.02 mg/kg for soil. A direct relationship was observed between the fluoride concentration in water and the amounts found in tomatoes, cucumbers, and onions. The estimated total dietary fluoride intake for children during summer and spring was 120.6 and 145.6 µg/kg/day, respectively. For adults, these values were 99.2 and 112 µg/kg/day. This study indicated that drinking water was the primary source of dietary fluoride intake in the study area. Furthermore, the hazard quotient (HQ) values for both adults and children were found to be greater than 1, confirming a potential health risk of fluorosis.